Ergot alkaloid glycosides with immunomodulatory activities - Kren, V; Fiserová, A; Augé, C; Sedmera, P; Havlícek, V; Síma, P (Bioorganic & medicinal chemistry, 1996)
New glycosides derived from ergot alkaloids elymoclavine and DH-lysergol were synthesized by chemoenzymatic methods. beta-Glucosides were obtained either by chemical method or by transglycosylation (glycosidase from Aspergillus oryzae), lactosides were prepared by further extension of carbohydrate chain using beta-1,4-galactosyltransferase (bovine milk) and alpha-5-N-acetylneuraminyl-(2-->6)-beta-D-galactopyranosyl-(l-->4)-2- acetamido-2-deoxy-beta-D-glucopyranosyl-(1-->O)-elymoclavine was prepared using alpha-2,6-sialyltransferase (rat liver). Immunomodulatory activity of elymoclavine and 9,10-dihydrolysergol and their glycosylated derivatives on natural killer (NK) cell-mediated cytotoxicity of human resting and activated human peripheral blood mononuclear cells (PBMC) was investigated. Addition of ergot alkaloid glycosides to the mixtures of effector and target cells potentiated the PBMC cytotoxicity against both NK-sensitive and -resistant target cells. The glycoconjugates of elymoclavine enhanced cytotoxicity of PBMC against NK-resistant target cells. The glycoconjugates of DH-lysergol potentiated NK cytotoxicity of PBMC against NK-sensitive target cells.
Keywords: spektrometrie hmotnostní - bombardování rychlými atomy; ergoliny; Glycosides; sacharidové sekvence; molekulární sekvence - údaje; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; cytotoxicita imunologická; Spectrometry, Mass, Fast Atom Bombardment; krysa rodu Rattus; Ergot Alkaloids; kultivované buňky; Adjuvants, Immunologic; Animals; lidé; námelové alkaloidy; Humans; adjuvancia imunologická; zvířata; buňky NK; Ergolines; Rats; nádorové buňky kultivované; Carbohydrate Sequence; Cells, Cultured; Molecular Sequence Data; Tumor Cells, Cultured; Killer Cells, Natural; Cytotoxicity, Immunologic; glykosidy